rút gọn: ( x ² – 5x + 1) ² + 2( 5x – 1) ( x ² – 5x + 1) + (5x- 1)

Question

rút gọn:
( x ² – 5x + 1) ² + 2( 5x – 1) ( x ² – 5x + 1) + (5x- 1)

in progress 0
Faith 1 tuần 2021-08-29T15:06:19+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-08-29T15:07:19+00:00

    Bạn xem hình

     

    0
    2021-08-29T15:07:24+00:00

    ( x ² – 5x + 1) ² + 2( 5x – 1) ( x ² – 5x + 1) + (5x- 1)

    =( x ² – 5x + 1) ²+( 5x – 1) ( x ² – 5x + 1) +( 5x – 1) ( x ² – 5x + 1) + (5x- 1)

    =(x ² – 5x + 1)( x ² – 5x + 1+5x-1)+( 5x – 1)(x ² – 5x + 2)

    =(x ² – 5x + 1)x ² +( 5x – 1)(x ² – 5x + 2)

    =(x ² – 5x + 1)x ²+(x ² – 5x + 1)5x+5x-x ² +5x -1-1

    =$x^{4}$ -5$x^{3}$ +$x^{2}$ +5$x^{3}$ -25$x^{2}$+5x -x ²+10x-2

    =$x^{4}$ -25$x^{2}$ +15x-2

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )